The Effect of Work Safety on Employee Performance - Mimma Ayu Nindhitaputri; Ida Nurnida (Almana : Jurnal Manajemen dan Bisnis, 2020)
Employees in a company are an asset that is strictly maintained and developed because they have a very important role in achieving an achievement or goal of the company. A description of the safety situation in PT. PLN (Persero) PUSHARLIS UWP IV Bandung in 2017: there were 8 workplace accidents that occurred with the time lost due to injury as much as 82 hours. Based on observations researchers saw that the lighting facilities in the office were less utilized and they also found there were some employees who ignored workplace safety by working without personal protective equipment. This study aims to determine the effect of work safety on employee performance in PT. PLN (Persero) PUSHARLIS UWP IV Bandung. This research used the descriptive-causal method, with the saturated sampling technique. The research analysis used descriptive analysis and simple regression analysis. Based on the results of the study, it can be concluded that the effect of work safety on employee performance in PT. PLN (Persero) PUSHARLIS UWP IV Bandung is in a good category, and it significantly has an effect on employee performance with a contribution equal to 21.2%.